(untitled) (Philosophy and Progress, 2025)
This article will try to explore the practical applications of Stoic philosophy, emphasizing its relevance in enriching life and assisting individuals to face real-life challenges. Stoicism, an ancient school of thought, dedicates in putting philosophical knowledge into action to strengthen the inner self and attain emotional resilience. This study explores Stoic teachings on managing emotions, distinguishing between what belongs within our control and what does not. Additionally, the article highlights the four cardinal virtues of Stoicism—wisdom, courage, justice, and temperance, which are essential principles for leading a meaningful life. Focusing on scholarly quotes from notable Stoic figures, the discussion has a motivation to face the adversities of life with a resilient mind. A short introduction to the origins and nature of Stoic philosophy is provided herewith, which will help readers to understand the foundational spirit of the Stoic philosophy. Overall, this article is an attempt to present Stoicism as an art of living that promotes resilience along with virtue. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 145-166